Etiologies and Treatment Burden in Adult Patients with Pure Red Cell Aplasia: A Single-Center Experience and Review of Literature - Pimjai Niparuck; Wasana Kanoksil; Pathawut Wacharapornin; Pichika Chantrathammachart; Sarinya Boongird (Anemia, 2020)
Background. Pure red cell aplasia (PRCA) is less common blood disorder; the causes and the treatments of PRCA are varied. Methods. We conducted a retrospective study during January 2010–December 2017, to explore the etiologies and to evaluate the response and treatment burden in adult patients with PRCA. Results. Of 32 PRCA patients, median age was 57 years (18–90 years). Median hemoglobin level and reticulocyte count at the time of diagnosis were 5.6 g/dL (3.3–7.3 g/dL) and 0.3% (0.1–0.7%), respectively. Median time to hematologic recovery was 12 weeks (3–72 weeks), and median number of red blood cell transfusion (RBC) was 20 units (4–100 units). Causes of PRCA were erythropoiesis-stimulating agent (ESA) (47%), parvovirus B19 infection (19%), thymoma (13%), zidovudine (6%), primary autoimmune PRCA (6%), Kaposi’s sarcoma (3%), systemic lupus erythematosus (3%), and ABO-mismatched stem cell transplantation (3%). Only 9 out of 24 treated patients achieved hematologic response within 8 weeks of treatment. Intravenous immunoglobulin therapy provided 100% response rate in patients with parvovirus B19-associated PRCA and primary autoimmune PRCA. Low response rate was found in patients receiving immunosuppressants and chemotherapy for the treatment of ESA and thymoma-associated PRCA, respectively. Conclusions. Treatment outcome of PRCA depended upon the causes and the types of treatment, and the burden of RBC transfusion was very high in patients with ESA and thymoma-associated PRCA.